Predictors of physical activity in older adults 65 years and older: findings in health survey of the Valencian Community - Trujillo-Barberá, Silvia; García-Martínez, Pedro; Sánchez-Martínez, Juana María; Rodríguez-Herrera, María Ángeles; Ruiz-Hontangas, Antonio; Gámez-Paya, Javier (Frontiers in Public Health, 2023)
Background: Physical activity is part of a healthy lifestyle in the elderly and is related to multiple variables that promote this behavior.Objective: To identify the relationship and predictive power of sociodemographic variables, multimorbidity, severity index, risk of poor mental health, social support, affective support and confidential support with the time devoted to physical activity in the population over 65 years of age in the Valencian Community.Methods: Cross-sectional descriptive analytical study of the data collected in the Health Survey of the Valencian Community on a total of 3199 people over 65 years of age. The study variables were age, sex, educational level, marital status, social class, multimorbidity, severity index collected with the EQ-5D-5L tool, risk of poor mental health collected with the Goldberg general health questionnaire (GHQ-12), and perceived social, affective and confidential support collected with the Duke-Unc social support scale (Duke-UNC-11).Results: All variables, except affective support, are significantly related to the time of physical activity performed by people older than 65 years. The severity index has a predictive capacity of 13.7% of physical activity performed and age is able to predict 1.2% of this variable. Conclusion: Sex, age, education, social class, marital status, multimorbidity, risk of poor mental health or social support and confidentiality are related to the physical activity time of the Valencian population over 65 years of age. On the other hand, the variables severity index and age have been 2 This is a provisional file, not the final typeset article identified as variables capable of predicting up to 14.8% of the variance of the physical activity time variable in our study population.